A = [-3, -2, -1, 3, 1, 2, 0]
B = [-3, -2, -1, 0, 1, 2, 3]
1) A.pop()
A = [-3, -2, -1, 3, 1, 2]
2) A.pop()
A = [-3, -2, -1, 3, 1]
3) A.pop()
A = [-3, -2, -1, 3]
4) A.pop()
A = [-3, -2, -1]
5) A.append(0)
A = [-3, -2, -1, 0]
6) A.append(1)
A = [-3, -2, -1, 0, 1]
7) A.append(2)
A = [-3, -2, -1, 0, 1, 2]
8) A.append(3)
A = [-3, -2, -1, 0, 1, 2, 3]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
A = [-3, -2, -1, 3, 1, 2, 0]
B = [-3, -2, -1, 0, 1, 2, 3]
1) A.pop()
A = [-3, -2, -1, 3, 1, 2]
B = [-3, -2, -1, 0, 1, 2, 3]
2) A.pop()
A = [-3, -2, -1, 3, 1]
B = [-3, -2, -1, 0, 1, 2, 3]
3) A.pop()
A = [-3, -2, -1, 3]
B = [-3, -2, -1, 0, 1, 2, 3]
4) A.pop()
A = [-3, -2, -1]
B = [-3, -2, -1, 0, 1, 2, 3]
5) A.append(0)
A = [-3, -2, -1, 0]
B = [-3, -2, -1, 0, 1, 2, 3]
6) A.append(1)
A = [-3, -2, -1, 0, 1]
B = [-3, -2, -1, 0, 1, 2, 3]
7) A.append(2)
A = [-3, -2, -1, 0, 1, 2]
B = [-3, -2, -1, 0, 1, 2, 3]
8) A.append(3)
A = [-3, -2, -1, 0, 1, 2, 3]
B = [-3, -2, -1, 0, 1, 2, 3]